Accuracy of Multiparametric Magnetic Resonance Imaging (MRI) in Determining Prostate Malignancy Based on Histopathological Results - Hendrick Revian; Mirna Muis; Rafikah Rauf; Muhammad A.A. Palinrungi; Andi A. Zainuddin (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2023)
Background: Prostate cancer is the most common malignancy in men in many regions of the world and is the second cause of cancer death in men as well as the third most common urological cancer in Indonesian men. One of the radiology examinations used to detect prostate cancer is multiparametric MRI which is a series of prostate magnetic resonance combining anatomical and functional imaging to detect and characterize prostate lesions. Purposes: This study aims to assess the accuracy of multiparametric prostate MRI in detecting prostate cancer based on the results of histopathological examination. Methods: This research used sensitivity value, specificity value, positive prediction value, and negative prediction value as well as Chi-Square test (P value < 0.05) to assess accuracy in SPSS program version 25. Results: This research was conducted at the central radiology installation of Dr. Wahidin Sudirohusodo Hospital and Hasanuddin University Hospital Makassar from February 2022 to July 2022, with 40 samples were obtained. Most samples were at the age of 60-70 years with 18 samples (45%), the most common lesion site was in the transitional zone with 19 samples (47.5%), multiparametric MRI results were predominant in the PIRADS 2 group with total sample of 18 (45%), PIRADS grading was obtained from benign categories (PIRADS 1 and 2) as much as 18 samples (45%) and from malignancy categories (PIRADS 3-5) with 22 samples (55%). Histopathological examination obtained benign results (BPH and prostatitis) in 21 samples (52.50%) and malignant in 19 samples (47.5%). Conclusion: We found correlation between multiparametric prostate MRI dan histopathological results by using bivariate correlation test with p values < 0.001. Multiparametric prostate MRI sensitivity value 100%, specificity 85.7%, positive prediction value 83.3%, Negative Prediction Value 100%, and accuracy 92.5%.